2021
DOI: 10.3390/su13094921
|View full text |Cite
|
Sign up to set email alerts
|

Training Freshmen Engineers as Managers to Develop Soft Skills: A Person-Centred Approach

Abstract: This article describes a subject design to train engineer students in soft skills through an experiential and person-centred approach, as is usually developed in companies for managers to incorporate responsible and ethical engineering perspectives. This design is based on an experiential methodology and its impact on students is presented. The subject, called “Personal and Professional Effectiveness”, was designed and developed based on Covey’s classic book “The 7 habits of highly effective people” and introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Generally speaking, the criteria for determining whether a skill is soft or hard depend on the context in which the skill is used. Some researchers argued that soft skills are often seen as being more “Person-Centred” whereas hard skills are classified as “Task-Centred”, emphasising the need for individuals to be able to both interact with and help others ( Rodríguez-Jiménez et al 2021 ). As a result, soft skills are typically viewed as more important when it comes to interpersonal aspects of professional life such as communication, problem-solving, customer service, and teamwork, among others.…”
Section: Critical Literature Reviewmentioning
confidence: 99%
“…Generally speaking, the criteria for determining whether a skill is soft or hard depend on the context in which the skill is used. Some researchers argued that soft skills are often seen as being more “Person-Centred” whereas hard skills are classified as “Task-Centred”, emphasising the need for individuals to be able to both interact with and help others ( Rodríguez-Jiménez et al 2021 ). As a result, soft skills are typically viewed as more important when it comes to interpersonal aspects of professional life such as communication, problem-solving, customer service, and teamwork, among others.…”
Section: Critical Literature Reviewmentioning
confidence: 99%
“…Research has shown that self-efficacy beliefs are important mediators of all types of achievement-related behaviors, such as effort and task persistence or self-regulatory strategies, among others (Meece et al, 2006). In this sense, educational programs have the possibility to enhance students' self-efficacy (Cuthbert, 1995;Heikkilä & Lonka, 2006;Van Dinther et al, 2011;Onah et al, 2020;López-Crespo et al, 2021;Rodríguez-Jiménez et al, 2021). Furthermore, findings from recent studies also shed new light on the undervalued and frequently occluded role of positive emotions in the writing process (Sword et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue sets out different educational methods and formats for bringing university students closer to the ideals of sustainability in its different environmental, economic and social dimensions. Some papers present experiences in educational activities or program design [1][2][3], teaching-learning sequences [4], learning contexts that facilitate ESD [5][6][7][8] or a person-centered approach to professional soft skills development [9]. Others analyze the sustainability competence status at the study level [10][11][12] and faculty level [13,14], student perception and knowledge of sustainability learning [15][16][17][18][19], or likewise propose strategies at the university level for the integration of sustainability and the Sustainable Development Goals (SDGs) [20] in degree curricula [21][22][23].…”
mentioning
confidence: 99%
“…The design of the subject "Personal and Professional Effectiveness" was based on Covey's classic book The 7 Habits of Highly Effective People [24]. This paper, proposed by Rodríguez-Jiménez and colleagues [9], provided a detailed description of the activities carried out during the course and analyzed the students' perceptions. They reflected on how the recognition of students' strengths and difficulties influences the development of an engineering work group for sustainability.…”
mentioning
confidence: 99%